Phase equilibria in ternary (carbon dioxide plus tetrahydrofuran plus water) system in hydrate-forming region: Effects of carbon dioxide concentration and the occurrence of pseudo-retrograde hydrate phenomenon - Khalik M., Sabil (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 24-28 OVAL RD, LONDON NW1 7DX, ENGLAND, 2010)
Abstract: In the present work, the three- and four-phase hydrate equilibria of (carbon dioxide (CO2) + tetrahydrofuran (THF) + water) system are measured by using Cailletet equipment in the temperature and pressure range of (272 to 292) K and (1.0 to 7.5) MPa, respectively, at different CO2 concentration. Throughout the study, the concentration of THF is kept constant at 5 mol% in the aqueous solution. In addition, the fluid phase transitions of L-w-L-v-V -> L-w-L-v (bubble point) and L-w-L-v-V -> L-w-V (dew point) are determined when they are present in the ternary system. For comparison, the three-phase hydrate equilibria of binary ( CO2 + H2O) are also measured. Experimental measurements show that the addition of THF as a hydrate promoter extends hydrate stability region by elevating the hydrate equilibrium temperature at a specified pressure. The three-phase equilibrium line H-L-w-V is found to be independent of the overall concentration of CO2. Contradictory, at higher pressure, the phase equilibria of the systems are significantly influenced by the overall concentration of CO2 in the systems. A liquid-liquid phase split is observed at overall concentration of CO2 as low as 3 mol% at elevated pressure. The region is bounded by the bubble-points line (L-w-L-v-V -> L-w-L-v), dew points line (L-w-L-v-V -> L-w + V) and the four-phase equilibrium line (H + L-w + L-v + V). At higher overall concentration of CO2 in the ternary system, experimental measurements show that pseudo-retrograde behaviour exists at pressure between (2.5 and 5) MPa at temperature of 290.8 K. (C) 2009 Published by Elsevier Ltd.